Nationalism and cultural practice in the postcolonial world - Lazarus, Neil (Cambridge University Press, 1999)
This wide-ranging study contains individual chapers on modernity, globalization and the "West," nationalism and decolonization, cricket and popular consciousness in the English-speaking Caribbean, and African pop music. Neil Lazarus offers extended discussions of the work of such influential writers, critics and activists as Frantz Fanon, C. L. R. James, Edward Said, Gayatri Spivak, Samir Amin, Raymond Williams, Paul Gilroy and Partha Chatterjee. This book is a politically focused, materialist intervention into postcolonial and cultural studies, and constitutes a major reappraisal of the debates on politics and culture in these fields